Habitual Physical Activity and Sleep Duration in Institutionalized Older Adults - Vogel, Oliver; Niederer, Daniel; Wilke, Jan; El-Rajab, Inaam; Vogt, Lutz (Frontiers in Neurology, 2021)
ABSTRACT BACKGROUND: Physical activity and sleep quality are both major factors for improving one’s health. Knowledge on the interactions of sleep quality and the amount of physical activity may be helpful for implementing multimodal health interventions in older adults. METHODS: This preliminary cross-sectional study is based on 64 participants (82.1 ± 6.4 years (MD ± SD); 22 male: 42 female). The amount of physical activity was assessed by means of an accelerometer (MyWellness Key). Self-reported sleep parameters were obtained using the Pittsburgh Sleep Quality Index. The Barthel Index was used for physical disability rating. Bivariate correlations (Spearman’s Rho) were used to explore relationships between the amount of physical activity and sleep quality. To analyse differences between categorial subgroups univariate ANOVAs were applied; in cases of significance, these were followed by Tukey-HSD post-hoc analyses. RESULTS: No linear association between physical activity and sleep quality was found (r = .119; p > .05). In subgroup analyses (n = 41, Barthel Index ≥ 90 pts, free of pre-existing conditions), physical activity levels differed significantly between groups of different sleep duration (≥ 7h; ≥ 6-< 7h; ≥ 5-< 6h; < 5h; p = .037). CONCLUSION: There is no general association between higher activity levels and better sleep quality in the investigated cohort. However, a sleep duration of ≥ 5-< 6 hours, corresponding to 7.6 hours bed rest time, was associated with a higher level of physical activity.